2021
DOI: 10.1007/s12104-021-10049-0
|View full text |Cite
|
Sign up to set email alerts
|

NMR chemical shift assignments of RNA oligonucleotides to expand the RNA chemical shift database

Abstract: RNAs play myriad functional and regulatory roles in the cell. Despite their significance, three-dimensional structure elucidation of RNA molecules lags significantly behind that of proteins. NMR-based studies are often rate-limited by the assignment of chemical shifts. Automation of the chemical shift assignment process can greatly facilitate structural studies, however, accurate chemical shift predictions rely on a robust and complete chemical shift database for training. We searched the Biological Magnetic R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Chemical shifts were suggested to be used to refine RNA structures [69] or decode structural features, such as solvent exposure, base stacking, or base pairing [70]. Liu et al have identified, designed, and assigned sequences with no or limited chemical shift information to help populate the Biological Magnetic Resonance Data Bank [71]. For a more thorough description of the integration of solutionstate NMR with computational techniques that aim at the improved and faster description of dynamic RNA ensembles, the reader is directed to the recent review by Liu et al [72].…”
Section: Methodological Developmentsmentioning
confidence: 99%
“…Chemical shifts were suggested to be used to refine RNA structures [69] or decode structural features, such as solvent exposure, base stacking, or base pairing [70]. Liu et al have identified, designed, and assigned sequences with no or limited chemical shift information to help populate the Biological Magnetic Resonance Data Bank [71]. For a more thorough description of the integration of solutionstate NMR with computational techniques that aim at the improved and faster description of dynamic RNA ensembles, the reader is directed to the recent review by Liu et al [72].…”
Section: Methodological Developmentsmentioning
confidence: 99%
“…The GAGA tetraloop is structurally stable and yields characteristic and unambiguous signals in the 2D 1 H-1 H NOESY spectra, which serve as an indicator of proper folding of the RNA and facilitate resonance assignments. 42,43 The observed NOE signals of NPSL2_Frag1 revealed that it adopted an A-form helical stem with a properly folded GAGA tetraloop (Fig. S4).…”
Section: Oligonucleotide-based Approach To Facilitate Resonance Assig...mentioning
confidence: 98%
“…These advancements have been facilitated by several key developments in NMR instrumentation, RNA sample preparation, data acquisition, and data analysis. These include the commercial availability of high-field magnets with up to 1.2 GHz 1 H Larmor frequency (28.2 T) [78] , the introduction of cryogenically cooled probes [79] , the implementation of non-uniform sampling and associated processing algorithms [80] , novel strategies for RNA synthesis and selective isotope labeling [ [74] , [75] , [77] , [81] ], the design of tailored NMR experiments for specific isotope labeling schemes [ [82] , [83] ], and the automation of resonance assignment and structure calculation [ [84] , [85] ]. The ongoing development of NMR methods has been accompanied by many significant applications of NMR in determination of both 2D and 3D structures of large RNAs.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%